GAME EDUKASI QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK PERKEMBANGAN TEKNOLOGI TRANSPORTASI PADA SISWA KELAS TIGA SEKOLAH DASAR - Nahdhiah, Umi; Supriyono; Rahayuningsih, Sri; Untari, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to improve thematic learning outcomes of transportation technology development materials using Quizizz educational games. This research method is classroom action research carried out in two research cycles, each consisting of four stages including planning, implementation, observation, and reflection stages. The subjects in this study were 20 elementary school third-grade students. Data collection in research is carried out using test methods, observation, and interviews with research instruments in the form of thematic learning outcomes tests. The data obtained from the study was then analyzed with qualitative and quantitative descriptive analysis techniques. The success indicator is set at 75% of students' learning outcomes complete KKM ≥75. The results of the study showed that the percentage of complete achievement of KKM in the pre-cycle was 25% to 40% in cycle I and 85% in cycle II. So it can be concluded that there is an increase in student learning outcomes after using the Quizizz educational game.